The Anushastra in Shalya Tantra: Clinical Usage - Kumari Damor, Suman; Narayan Meena, Namo; Kumar Soni, Rajesh (International Research Journal of Ayurveda & Yoga, 2025)
Anushastra refers to a category of parasurgical procedures. These operations differ from major surgeries, particularly for patients who are sensitive to shastra karma. The objective is to investigate traditional parasurgical techniques used across various conditions, alongside surgical methods. The present theoretical study examines the application of parasurgical techniques found in contemporary literature, known as Anushastra. This article outlines the approaches for executing three key parasurgical procedures. The various types of Anushastra hold significant relevance in the classical texts of Ayurveda and continue to be employed in treatments for various health issues. Specific anorectal conditions are suitable for shastra interventions, involving the application of energy to treat different ailments. Two techniques are described: shastrakrita siravedha and prachana methods for ajashakrit, danta, shalaka (samples), and ghrita Raktamokshana. In addition, ghati and ashastrakrita techniques are also included – Anushastra is becoming more recognized in the management of chronic illnesses.